Science: A Race without a Finish. The Position of Europe - Peter Nijkamp (Romanian Journal of European Affairs, 2005)
This paper addresses the fundamentals of our knowledge-based society, with a particular view to the emerging new knowledge initiatives in the European Union. After a discussion of the current R&D investment trends in Europe, several flaws in the European knowledge system and in the European Research Area (ERA) are highlighted. The need for a drastic improvement of frontier research (i.e. excellence-driven research) and for a better coordination of the great many research initiatives in the widening European Union is emphasized. A drastic change is needed in order to cope with the fragmentation and the sometimes low R&D intensity in the ERA. The paper concludes with a presentation of a recent meta-analysis which demonstrates the importance of public expenditures for education and research, based on a comparative analysis of 123 applied studies on the impact of government expenditures for knowledge investments on economic growth.